Pelagomanes cantharoides, n. comb. - Trubovitz, Sarah; Renaudie, Johan; Lazarus, David; Noble, Paula (Geoscientific Model Development, 2022)
Pelagomanes cantharoides (Sugiyama and Furutani, 1992) n. comb. Plate 40, Figs. 1–3, 7–8, 10, 14. Ceratocyrtis? cantharoides n. sp., Sugiyama and Furutani, 1992, pl. 13, figs. 1–2; pl. 20, figs. 1–2b. Ceratocyrtis sp. aff. C. cucullaris (Ehrenberg), Tsoy and Shastina, 1999, pl. 35, fig. 6. Ceratocyrtis? cantharoides Sugiyama and Furutani, Renaudie, 2014, pl. 22, fig. 3. Ceratocyrtis cantharoides Sugiyama and Furutani, Trubovitz et al., 2020, supplementary data 7. Remarks. Sugiyama and Furutani (1992) only tentatively placed this species in Ceratocyrtis because it lacks the well-developed, dendritic axobate that is typical of Ceratocyrtis species. The authors state that the apical horn has 1–2 branches on the dorsal side. It is this forked apical horn that separates P. cantharoides from similar taxa (i.e., P. morawanensis and P. tekopua ). However, it is unclear whether this character alone should justify the separation of this species from P. morawanensis (Funakawa). Plate 40 demonstrates that specimens sharing the character of a forked apical horn often have as many differences between one another as with specimens without a forked horn. This suggests that a forked horn may not be a reliable distinguishing character, and these two species concepts may require revision. Here we provisionally accept these two concepts as separate species, but acknowledge that further study may show they are the same. Range. Middle Miocene in the EEP, though the range in our material is not well constrained (Table 1). Sugiyama and Furutani (1992) described this species from the Middle Miocene of Japan. Renaudie (2014) reported it from the Early–Middle Miocene of the Southern Ocean. Published as part of Trubovitz, Sarah, Renaudie, Johan, Lazarus, David & Noble, Paula, 2022, Late Neogene Lophophaenidae (Nassellaria, Radiolaria) from the eastern equatorial Pacific, pp. 1-158 in Zootaxa 5160 (1) on page 80, DOI:10.11646/zootaxa.5160.1.1, http://zenodo.org/record/10544058